CORPORATE RESPONSE TO CONCEPT OF SHARED VALUE - Kreckova, Zuzana (European Scientific Journal, ESJ, 2015)
Recent decades show that pure profit-maximization cannot be the best way for corporate long-term growth. Shareholders golden period is gone. Changed strength of stakeholders is forcing top managers to search for new avenues where profit maximization will be accompanied with value creation that will meet societal needs. The phenomenon of Shared values seems to be the answer. The article analyses successful companies that adopted the concept and brings general conclusions of their successful ways.